2021
DOI: 10.3390/cells10050995
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Endoplasmic Reticulum Stress Marker GRP78 in the Normal Retina and Retinal Degeneration Induced by Blue LED Stimuli in Mice

Abstract: Retinal degeneration is a leading cause of blindness. The unfolded protein response (UPR) is an endoplasmic reticulum (ER) stress response that affects cell survival and death and GRP78 forms a representative protective response. We aimed to determine the exact localization of GRP78 in an animal model of light-induced retinal degeneration. Dark-adapted mice were exposed to blue light-emitting diodes and retinas were obtained at 24 h and 72 h after exposure. In the normal retina, we found that GRP78 was rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…It has been reported that the GRP78/Bip is mainly localized in thin cytoplasmic components within the intercellular spaces, which might be process of Müller glial cells. 27 Moreover, they were distributed throughout the nuclear membrane and might be the ER ( Fig. 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the GRP78/Bip is mainly localized in thin cytoplasmic components within the intercellular spaces, which might be process of Müller glial cells. 27 Moreover, they were distributed throughout the nuclear membrane and might be the ER ( Fig. 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…This result may support the idea that the UPR includes two phases 28 : early UPR, which can suppress ER stress and restore ER homeostasis, and late UPR, which is too severe to restore ER homeostasis and leads to apoptotic cell death. 27 In the initial exposure stage, the retinas experience external stress during early UPR, but the ER stress cannot restore ER homeostasis, probably due to the intense blue light toxicity in the CL that causes cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the viability of cells was decreased, and the GRP78 and caspase-12 of ER stress-related proteins were upregulated in HG-treated HT22 cells. GRP78 and caspase-12 are two key hallmarks of ER stress [37,38]. A recent work demonstrated that hyperglycemia-induced ER stress plays a critical role in the development of diabetic encephalopathy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the vitreous humors from diabetic patients revealed increased expression of MALAT1 accompanied by increased levels of TNF-α and IL-6 [ 48 ]. Moreover, MALAT1 knockdown in human retinal vascular endothelial cells (RVECs) grown in HG—displaying high levels of MALAT1 , glucose-regulated protein 78 (GRP78) and C/EBP homologous protein (CHOP)—reduces both capillary morphogenesis and the inflammation, suggesting that this lncRNA can promote angiogenesis and inflammation by upregulating retinal endoplasmic reticulum stress [ 49 , 50 ]. Another mechanism, possibly underlying the effects of MALAT1 on inflammatory genes expression, is the association with the master catalytic subunit of the methyltransferase polycomb repressive complex 2 (PRC2) and the consequent regulation of epigenetic mediators [ 48 ].…”
Section: Long Non Coding Rnas With Increased Expression In Diabetic R...mentioning
confidence: 99%